FILTERS INTERNET TRAFFIC IN EDUCATION - Nadezhda M. Akchurina; Gennady V. Slyusarev (Вестник Северо-Кавказского федерального университета, 2022)
Extensive penetration of Internet in education opened opportunities for students to access potentially dangerous content with extremist, terrorist and antisocial orientation. Therefore, it becomes necessary to restrict access, to monitor and analyze Internet traffic.